The Incidence and Risk Factors of Intra- operative Nausea and Vomiting after Cesarean Section under Spinal Anesthesia - Samadi, Kazem; Kheirandish, Saba; Sadeghi, Seyed Ebrahim; Kalani, Navid; Moradi, Atosa (International Journal of Psychosocial Rehabilitation, 2020)
-- Background: Nausea and vomiting is a common postoperative complication after general anesthesia, while spinal anesthesia may be associated with intra-operative nausea and vomiting (IONV), as well. Several factors affect the incidence of IONV that have to be considered for prevention of this complication. Considering the racial differences in the incidence of IONV, and different drug efficacy and adverse effects, we aimed to determine the incidence and risk factors of IONV in patients undergoing cesarean sections (C/S) under spinal anesthesia in an Iranian population.Methods: This cross-sectional study was conducted on 500 pregnant women who underwent C/S under spinal anesthesia. The collected data included demographics (age, educational level, body mass index [BMI], and number of pregnancies), history of gastrointestinal diseases, migraine headaches, anxiety (evaluated by Beck Anxiety Inventory), hypertension, nausea and vomiting (N/V) and vaginal bleeding during pregnancy, and NPO state, as well as the type and dosage of spinal anesthetic, use of ephedrine for blood pressure control, needle size, and sex of the neonate.Results: There was a significant association between IONV and hyperemesis, anxiety, ephedrine use, and eclampsia (P0.05). Backward logistic regression indicated that ephedrine usage, history of hyperemesis, eclampsia, and anxiety were independently and significantly associated with IONV.Conclusions: Appropriate treatment of conditions that are associated with IONV before C/S, including ephedrine usage, history of hyperemesis, eclampsia, and anxiety, can be effective in preventing this annoying complication.• Veiga-Gil L, Pueyo J, Lopez-Olaondo Postoperative nausea and vomiting: physiopathology, risk factors, prophylaxis and treatment. Rev Esp Anestesiol Reanim 2017;64(4):223-32.• Gan TJ. Risk factors for postoperative nausea and vomiting. Anesth Analg 2006;102(6):1884-98.• Tan A, Lowe S, Henry A. Nausea and vomiting of pregnancy: Effects on quality of life and day-to-day function. Aust N Z J Obstet Gynaecol 2018;58:278-90.• Voigt M, Frohlich CW, Huttel C, Kranke P, Mennen J, Boessneck O, et al. Prophylaxis of intra- and postoperative nausea and vomiting in patients during cesarean section in spinal anesthesia. Med Sci Monit 2013;19:993-1000.• Chatterjee S, Rudra A, Sengupta S. Current concepts in the management of postoperative nausea and vomiting. Anesthesiol Res Pract 2011;2011:748031.• Moon YE. Postoperative nausea and vomiting. Korean J Anesthesiol 2014;67(3):164-70. • Rusch D, Eberhart LH, Wallenborn J, Kranke P. Nausea and vomiting after surgery under general anesthesia: an evidence-based review concerning risk assessment, prevention, and treatment. Dtsch Arztebl Int 2010;107(42):733-41.• Pazouki A, Cheraghali R, Saeedimotahhar H, Jesmi F, Jangjoo A, Pishgahroudsari M. Pre-operative rectal indomethacin for reduction of postoperative nausea and vomiting after laparoscopic cholecystectomy: a double-blind randomized clinical trial. J Coll Physicians Surg Pak 2015;25(1):56-9.• Kim BG, Kim H, Lim HK, Yang C, Oh S, Lee BW. A comparison of palonosetron and dexamethasone for postoperative nausea and vomiting in orthopedic patients receiving patient-controlled epidural analgesia. Korean J Anesthesiol 2017;70(5):520-6.• Muchatuta NA, Paech MJ. Management of postoperative nausea and vomiting: focus on palonosetron. Ther Clin Risk Manag 2009;5(1):21-34.• Kim EJ, Ko JS, Kim CS, Lee SM, Choi DH. Combination of antiemetics for the prevention of postoperative nausea and vomiting in high-risk patients. J Korean Med Sci 2007;22(5):878-82.• Mishriky BM, Habib AS. Metoclopramide for nausea and vomiting prophylaxis during and after Caesarean delivery: a systematic review and meta-analysis. Br J Anaesth 2012;108(3):374-83.• Rodseth RN, Gopalan PD, Cassimjee HM, Goga S. Reduced incidence of postoperative nausea and vomiting in black South Africans and its utility for a modified risk scoring system. Anesth Analg 2010;110(6):1591-4.• Cepeda MS, Farrar JT, Baumgarten M, Boston R, Carr DB, Strom BL. Side effects of opioids during short‐term administration: Effect of age, gender, and race. Clin Pharmacol Ther 2003;74(2):102-12.• Sirajuddin M, Abbas N, Murtaza G, Naqvi SMN. Common Complaints Associated with Caesarean Section during Spinal Anaesthesia. Ann Abbasi Shaheed Hosp 2013;18(1):33-7.• Hossein Kaviani H, Mousavi AS. Psychometric properties of the Persian version of Beck Anxiety Inventory (BAI). Tehran-Univ-Med-J 2008;66:136-40.• Kadur SN, Ahmed F, Purohit A, Khandelwal M, Mistry T. The effect of intravenous dexamethasone on postoperative pain, nausea and vomiting after intrathecal pethidine and bupivacaine in lower limb orthopedic surgery. Anaesthesia, pain & intensive care 2015;19:254-9.• Magni BJ, Dyer RA, van Dyk D, van Nugteren J. Incidence of intraoperative nausea and vomiting during spinal anaesthesia for Caesarean section in two Cape Town state hospitals. SAJAA 2016;22:131-4.• Abouleish EI, Rashid S, Haque S, Giezentanner A, Joynton P, Chuang AZ. Ondansetron versus placebo for the control of nausea and vomiting during Caesarean section under spinal anaesthesia. Anaesthesia 1999;54(5):479-82.• Griffiths JD, Gyte GM, Paranjothy S, Brown HC, Broughton HK, Thomas J. Interventions for preventing nausea and vomiting in women undergoing regional anaesthesia for caesarean section. Cochrane Database Syst Rev 2012:Cd007579.• Stadler M, Bardiau F, Seidel L, Albert A, Boogaerts JG. Difference in risk factors for postoperative nausea and vomiting. Anesthesiology 2003;98:46-52.• Apfel C, Kranke P, Greim CA, Roewer N. What can be expected from risk scores for predicting postoperative nausea and vomiting? Br J Anaesth 2001;86(6):822-7.• Singh P, Yoon SS, Kuo B. Nausea: a review of pathophysiology and therapeutics. Therap Adv Gastroenterol 2016;9(1):98-112.• Manullang TR, Viscomi CM, Pace NL. Intrathecal fentanyl is superior to intravenous ondansetron for the prevention of perioperative nausea during cesarean delivery with spinal anesthesia. Anesth Analg 2000;90(5):1162-6.• Habib AS, Itchon-Ramos N, Phillips-Bute BG, Gan TJ. Transcutaneous acupoint electrical stimulation with the ReliefBand® for the prevention of nausea and vomiting during and after cesarean delivery under spinal anesthesia. Anesth Analg 2006;102(2):581-4.• Ho C-M, Tsai H-J, Chan K-H, Tsai S-K. P6 acupressure does not prevent emesis during spinal anesthesia for cesarean delivery. Anesth Analg 2006;102(3):900-3. • Dasgupta M, Biswas B, Chatterjee S, Mazumder P, Chowdhury MB. Randomized, placebo-controlled trial of granisetron for control of nausea and vomiting during cesarean delivery under spinal anesthesia. J Obstet Gynaecol India 2012;62(4):419-23.• Morino R, Ozaki M, Nagata O, Yokota M. Incidence of and risk factors for postoperative nausea and vomiting at a Japanese Cancer Center: first large-scale study in Japan. J Anesth 2013;27(1):18-24.• Van den Bosch JE, Moons KG, Bonsel GJ, Kalkman CJ. Does measurement of preoperative anxiety have added value for predicting postoperative nausea and vomiting? Anesth Analg 2005;100:1525-32.• Atanasova M, Hinev S. [Preoperative anxiety and its influence over the postoperative nausea and vomiting]. Khirurgiia (Sofiia) 2009:40-3.